Patients with wound around ostomy – nursing care aspects - Szewczyk, Maria T.; Cierzniakowska, Katarzyna; Cwajda, Justyna; Stodolska, Alina; Jawień, Arkadiusz; Banaszkiewicz, Zbigniew (Przewodnik Lekarza/Guide for GPs, 2005)
Patient with wound around ostomy needs complex approach and understanding from care team. Healing process may be complicated and long-lasting. It is painful, fatigue, and sometimes there’s a need of hospital admission. Care team implement many activities including appropriate choice of resources, exudate control, general treatment, nutrition interventions, suplementation, pain management and wide approach to psychological interventions: psychotherapy, social rehabilitation. All of these methods have vital role in treatment process. Due to difficulties of healing process very important is prevention of wound development – it is better to prevent than cure. These article also discusses principles of skin changes prevention.